Perceptions of corporate corruption culture and debt contracting - Hao, Jie; Pham, Viet; Sánchez, Daniela; Sánchez, Juan Manuel (Journal of Corporate Finance, 2021)
We find that the perception of corporate corruption culture in the top executive team affects both pricing and non-pricing loan provisions. Firms with higher levels of perceived corruption culture face higher interest spreads and are more likely to receive a collateral requirement. The bank syndicate is larger and more performance-based covenants and managerial negative restrictions (e.g., limits on capital expenditures or dividend restrictions) are put in place in loans made to firms with higher levels of perceived executive-based corruption. We further find that cultural proximity between lenders and borrowers mitigates the perceived corruption effects significantly, leading to contracts that are less costly and less restrictive. Additional tests suggest that lenders display an in-group bias in favor of culturally proximate borrowers.